PEMAHAMAN PESERTA PEMBEKALAN GURU KELAS/AGAMA DALAM MATA PELAJARAN PENJAS TERHADAP PENDIDIKAN JASMANI SD DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Dwi Marhaendro, Agus Susworo (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-top: 0cm; margin-right: -1.7pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 121%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">The aim of this research is to reveal a description on the participants’ understanding of teaching learning process in elementary physical education on the cognitive, affective, and psychomotor aspects. They were the participants of training for classroom/ religion teachers in Yogyakarta Special Province. The population was 80 classroom/ religion teachers who participated in the training of 2005. The sample was <p class="MsoNormal" style="margin-top: .1pt; margin-right: -1.35pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 121%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">60 teachers taken by purposive sampling procedures. This research employed descriptive approach using questionnaire as the data collection technique. The results showed that for cognitive aspect, it was 91, <p class="MsoNormal" style="margin-top: .1pt; margin-right: -1.35pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 121%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">67% of cognitive aspect categorized as high, 8,33% as medium, and 0% as low. It was 6,7 %of affective aspect categorized as high, 5 % as medium, and <p class="MsoNormal" style="margin-top: .1pt; margin-right: -1.6pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 121%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">18,33 % as low. It was 63,33% of psychomotor aspect categorized as high, 36,67% as medium, and 0% as low. The total of those three aspects showed that the understanding of the training participants were 43,33% included as high category, 56,67% included as medium category, and 0% included as low category. <p class="MsoNormal" style="margin-top: .25pt; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 0cm; line-height: 6.0pt; mso-line-height-rule: exactly; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;"> <p class="MsoNormal" style="margin-top: 0cm; margin-right: -1.4pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 128%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">Kata kunci: Pemahaman, Guru Kelas/Agama SD, Pembelajaran Pendidikan Jasmani